THE MARKET IS CALLING FOR BIOLAGE R.A.W - Loureiro, S. M. C.; Anes, P. (SAGE Business Cases, 2019)
Biolage R.A.W. is a professional haircare brand launched in Portugal in 2017. It uses natural ingredients in the composition of its products, providing a sensorial experience, without neglecting professional treatment. Although Portuguese citizens—particularly Millennials—have a positive attitude toward natural and sustainable products, they tend not to purchase such products, particularly within the category of haircare. Portuguese consumers do not attribute enough value to this product to justify a premium price. Within a limited budget, Biolage R.A.W. seeks to increase awareness of its brand, encouraging consumers to pay a premium for a natural and sustainable product while establishing a communication strategy target for natural products.